Method for determining correlation between surface pores of continuous casting billet and recarburization behavior of casting powder

By comparing the ferrite content and grain size of the pore defect area and the defect-free area on the surface of the continuous casting billet, the correlation between the pore defects and the carbonization behavior of the mold slag is determined, which solves the problem in the existing technology that it is difficult to accurately determine the cause of the pore defects. , achieving effective suppression of pore defects and improvement of billet surface quality.

CN119328090AActive Publication Date: 2025-01-21BAOSHAN IRON & STEEL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310882863.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-18
Publication Date
2025-01-21
Estimated Expiration
2043-07-18

AI Technical Summary

Technical Problem

The prior art is difficult to accurately judge the correlation between the pore defects on the surface of continuous casting billets and the carbon increase behavior of the protective slag, which makes it difficult to effectively suppress the pore defects and affect the surface quality of the billets.

Method used

By obtaining the metallographic structure images of the pore defect area and the pore defect area on the surface of the continuous casting billet, calculate the ferrite content and original austenite grain size in the two areas, and compare the difference between the two areas. If the ferrite content is less than If the defect-free area and the grain size are larger than the defect-free area, it is judged that the pore defects have a strong correlation with the carbonization behavior of the mold slag.

Benefits of technology

This method can simply and accurately determine the correlation between the stagnation of the pores of the connected blank surface and the carbon increase of the residue, which provides the basis for suppressing the formation of air pore defects, and improving the surface quality of the blank.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119328090A_ABST
    Figure CN119328090A_ABST
Patent Text Reader

Abstract

The invention discloses a method for determining correlation between surface pores of a continuous casting billet and recarburization behaviors of casting powder. The method comprises the following steps: S1, acquiring metallographic structure images of a pore defect area and a pore-free defect area on the surface of the continuous casting billet; s2, the ferrite content of the pore defect area and the ferrite content of the pore defect-free area are calculated; s3, calculating the original austenite grain size of the pore defect area and the pore-free defect area; s4, comparing the ferrite content of the pore defect area with the ferrite content of the non-pore defect area, and comparing the original austenite grain size of the pore defect area with the original austenite grain size of the non-pore defect area; and S5, if the ferrite content of the pore defect area is smaller than the ferrite content of the non-pore defect area and the original austenite grain size of the pore defect area is larger than the original austenite grain size of the non-pore defect area, the correlation between the pore defects on the surface of the continuous casting billet and the recarburization behavior of the casting powder is high, and otherwise, the correlation is low. The method solves the surface air hole defect of the continuous casting billet.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to continuous casting production technology, and more specifically to a method for determining the correlation between pores on the surface of a continuous casting billet and carbon enhancement behavior of protective slag. Background Art

[0002] As users' requirements for steel quality continue to improve, there are more stringent requirements for the quality level of continuous casting billets. The quality of continuous casting billets can be mainly divided into three parts: surface quality, internal quality and cleanliness. Among them, the pores on the surface of continuous casting billets are a common defect in surface quality, so it is of great significance to analyze the causes of pore defects.

[0003] At present, the common factors that cause pores are poor deoxidation, foreign gas elements, secondary oxidation, and continuous casting mold protection slag. At the same time, in actual production, the traceability of pore defects often has many uncertain factors and is difficult to accurately judge. Since poor deoxidation, foreign gas elements, secondary oxidation, etc. can often be reflected by the composition of molten steel, there is often a lack of better methods for protection slag. Protection slag has a direct impact on the control of the surface quality of continuous casting billets, and its role is even more critical in the stable production of high-quality steel. The functions of protection slag are usually manifested in five aspects: thermal insulation, prevention of secondary oxidation, absorption of inclusions, lubrication of billets, and control of heat transfer. When the protection slag is used improperly, surface defects such as bonding leakage, cracks, and pores will easily occur. Therefore, the normal manifestation of the protection slag function and the avoidance of its negative effects are very meaningful. Summary of the invention

[0004] In view of the defects existing in the prior art, the purpose of the present invention is to provide a method for determining the correlation between the surface pores of the continuous casting billet and the carbon increasing behavior of the protective slag, so as to solve the pore defects on the surface of the continuous casting billet and avoid the negative effects that may occur during the use of the protective slag, thereby facilitating the stable improvement of the surface quality of the continuous casting billet and better exerting the role of the protective slag.

[0005] To achieve the above object, the present invention adopts the following technical solution:

[0006] A method for determining the correlation between pores on the surface of a continuous casting billet and carbon enhancement behavior of mold slag comprises the following steps:

[0007] S1. Obtaining metallographic images of pore defect areas and pore-free defect areas on the surface of the continuous casting billet;

[0008] S2. Calculate the ferrite content in the pore defect area and the area without pore defect;

[0009] S3, calculating the original austenite grain size in the pore defect area and the pore defect-free area;

[0010] S4. Compare the ferrite content in the pore defect area with that in the area without pore defects, and compare the original austenite grain size in the pore defect area with that in the area without pore defects;

[0011] S5. If the ferrite content in the pore defect area is less than that in the area without pore defects, and the original austenite grain size in the pore defect area is larger than that in the area without pore defects, then the pore defects on the surface of the continuous casting billet are strongly correlated with the carbon enhancement behavior of the protective slag, otherwise the correlation is weak.

[0012] Preferably, before obtaining the metallographic structure image in step S1, the surface of the continuous casting billet needs to be processed:

[0013] After grinding and polishing the pore defect areas and non-pore defect areas on the surface of the continuous casting billet, the surface was corroded with nitric acid alcohol.

[0014] Preferably, in step S2 and step S3, the image processing software Image Pro Plus is used to calculate the ferrite content in the pore defect area and the area without pore defects, and to calculate the original austenite grain size in the pore defect area and the area without pore defects.

[0015] Preferably, the step S5 further comprises:

[0016] If the ferrite content in the pore defect area / the ferrite content in the non-pore defect area is less than 80%, and the original austenite grain size in the pore defect area / the original austenite grain size in the non-pore defect area is greater than 110%, then the pore defects on the surface of the continuous casting billet are strongly correlated with the carbon enhancement behavior of the protective slag, otherwise the correlation is weak.

[0017] The present invention provides a method for determining the correlation between the pores on the surface of a continuous casting billet and the carbon increase behavior of the mold slag. This determination method is simple, accurate, and highly applicable, and is of great significance for the stable improvement of the surface quality of the continuous casting billet. When the pores on the surface of the continuous casting billet are significantly correlated with the carbon increase behavior of the mold slag, the formation of pore defects on the surface of the continuous casting billet can be suppressed by reducing the carbon increase behavior of the mold slag. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic flow chart of the determination method of the present invention;

[0019] Figure 2 It is a schematic diagram of the morphology of the pore defect area on the surface of the continuous casting billet;

[0020] Figure 3 It is a schematic diagram of the metallographic structure of the pore defect area on the surface of the continuous casting billet;

[0021] Figure 4It is a schematic diagram of the metallographic structure of the area without pore defects on the surface of the continuous casting billet. DETAILED DESCRIPTION

[0022] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.

[0023] Combination Figure 1 As shown, the present invention provides a method for determining the correlation between the pores on the surface of a continuous casting billet and the carbon enhancement behavior of a mold slag, comprising the following steps:

[0024] S1. Obtaining metallographic images of pore defect areas and non-pore defect areas on the surface of the continuous casting billet;

[0025] S2. Calculate the ferrite content in the pore defect area and the area without pore defect;

[0026] S3, calculating the original austenite grain size in the pore defect area and the pore defect-free area;

[0027] S4. Compare the ferrite content in the pore defect area with that in the area without pore defects, and compare the original austenite grain size in the pore defect area with that in the area without pore defects;

[0028] S5. If the ferrite content in the pore defect area is significantly lower than that in the area without pore defects, and the original austenite grain size in the pore defect area is significantly larger than that in the area without pore defects, then the pore defects on the surface of the continuous casting billet are strongly correlated with the carbon enhancement behavior of the protective slag, otherwise the correlation is weak.

[0029] Before obtaining the metallographic structure image in step S1, the surface of the continuous casting billet needs to be processed:

[0030] After grinding and polishing the pore defect area and the non-pore defect area on the surface of the continuous casting billet, the surface was corroded with 4% nitric acid alcohol.

[0031] In step S2 and step S3, the image processing software Image Pro Plus is used to calculate the ferrite content in the pore defect area and the area without pore defects, and the original austenite grain size in the pore defect area and the area without pore defects is calculated.

[0032] Step S5 further comprises:

[0033] If the ferrite content in the pore defect area / the ferrite content in the non-pore defect area is less than 80%, and the original austenite grain size in the pore defect area / the original austenite grain size in the non-pore defect area is greater than 110%, when these two conditions are met at the same time, the pore defects on the surface of the continuous casting billet are strongly correlated with the carbon enhancement behavior of the protective slag, otherwise the correlation is weak.

[0034] Due to the carbon increase of molten steel, the carbon content in the area near the pores is relatively high, resulting in a smaller ferrite content. At the same time, the increase in carbon content in the initial stage of liquid-solid transformation causes the two-phase zone to become wider, thereby increasing the initial austenite grains. Therefore, the above characteristics will be the key basis for determining the correlation between the pores on the surface of the continuous casting billet and the carbon increase of the protective slag.

[0035] Example 1

[0036] Taking the surface pore defects of SCM435 cold heading steel (carbon content of 0.35%) continuous casting billet as an example, the method for determining the correlation between the surface pores of the continuous casting billet and the carbon enhancement behavior of the mold slag of this embodiment 1 includes the following steps:

[0037] S1. Use 4% nitric acid alcohol solution to clean the pore defect areas on the surface of the continuous casting billet (such as Figure 2 The samples of the area with pore defects (as shown in Figure 2) and the area without pore defects (normal area) were corroded, and their corresponding metallographic structure images were obtained, as shown in Figure 2. Figure 3 and Figure 4 As shown;

[0038] S2. Calculate the ferrite content in the pore defect area and the area without pore defects, which are 17.6% and 24.8% respectively;

[0039] S3, the original austenite grain sizes in the pore defect area and the area without pore defects are calculated to be 430.3μm and 379.2μm respectively;

[0040] S4. Comparing the ferrite content in the pore defect area with that in the area without pore defects, the proportion less than 29.0%; comparing the original austenite grain size in the pore defect area with that in the area without pore defects, the proportion greater than 13.5%;

[0041] Therefore, the ferrite content in the pore defect area / the ferrite content in the non-pore defect area is less than 80%, and the original austenite grain size in the pore defect area / the original austenite grain size in the non-pore defect area is greater than 110%;

[0042] S5. If these two conditions are met at the same time, the porosity defects on the surface of the continuous casting billet are strongly correlated with the carbon increase behavior of the protective slag, and the occurrence of surface porosity defects can be suppressed by weakening the carbon increase behavior of the protective slag.

[0043] Example 2

[0044] Taking the surface pore defects of SCM435 cold heading steel (carbon content of 0.35%) continuous casting billet as an example, the method for determining the correlation between the surface pores of the continuous casting billet and the carbon enhancement behavior of the mold slag of this embodiment 1 includes the following steps:

[0045] S1. Using 4% nitric acid alcohol solution to corrode the samples of the pore defect area and the non-pore defect area (normal area) on the surface of the continuous casting billet, and obtain their respective corresponding metallographic structure images;

[0046] S2. Calculate the ferrite content in the pore defect area and the area without pore defects, which are 21.3% and 22.5% respectively;

[0047] S3, the original austenite grain sizes in the pore defect area and the area without pore defects are calculated to be 375.4μm and 370.5μm respectively;

[0048] S4. Comparing the ferrite content in the pore defect area with that in the area without pore defects, the proportion is less than 5.3%, and comparing the original austenite grain size in the pore defect area with that in the area without pore defects, the proportion is greater than 1.3%;

[0049] Therefore, the ferrite content in the pore defect area / the ferrite content in the non-pore defect area is significantly greater than 80%, and the original austenite grain size in the pore defect area is very close to that in the non-pore defect area;

[0050] S5. If both conditions are not met, it indicates that the porosity defects on the surface of the continuous casting billet have a weak correlation with the carbon enhancement behavior of the protective slag.

[0051] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.

Claims

1. A method for determining the correlation between the pores on the surface of a continuous casting billet and the carbon enhancement behavior of mold slag, characterized in that: The following steps are involved: S1. Obtaining metallographic images of pore defect areas and non-pore defect areas on the surface of the continuous casting billet; S2. Calculate the ferrite content in the pore defect area and the area without pore defect; S3, calculating the original austenite grain size in the pore defect area and the pore defect-free area; S4. Compare the ferrite content in the pore defect area with that in the area without pore defects, and compare the original austenite grain size in the pore defect area with that in the area without pore defects; S5. If the ferrite content in the pore defect area is less than that in the area without pore defects, and the original austenite grain size in the pore defect area is larger than that in the area without pore defects, then the pore defects on the surface of the continuous casting billet are strongly correlated with the carbon enhancement behavior of the protective slag, otherwise the correlation is weak.

2. The method for determining the correlation between the pores on the surface of the continuous casting billet and the carburization behavior of the mold slag according to claim 1, characterized in that: Before obtaining the metallographic structure image in step S1, the surface of the continuous casting billet needs to be processed: After grinding and polishing the pore defect areas and non-pore defect areas on the surface of the continuous casting billet, the surface was corroded with nitric acid alcohol.

3. The method for determining the correlation between the pores on the surface of the continuous casting billet and the carburization behavior of the mold slag according to claim 1, characterized in that: In step S2 and step S3, the image processing software Image Pro Plus is used to calculate the ferrite content in the pore defect area and the area without pore defects, and the original austenite grain size in the pore defect area and the area without pore defects is calculated.

4. The method for determining the correlation between the pores on the surface of the continuous casting billet and the carburization behavior of the mold slag according to claim 1, characterized in that: The step S5 further comprises: If the ferrite content in the pore defect area / the ferrite content in the non-pore defect area is less than 80%, and the original austenite grain size in the pore defect area / the original austenite grain size in the non-pore defect area is greater than 110%, then the pore defects on the surface of the continuous casting billet are strongly correlated with the carbon enhancement behavior of the protective slag, otherwise the correlation is weak.

Citation Information

Patent Citations

  • Improved 40CrNiMo steel and preparation method thereof

    CN102242322A

  • Thick steel plate and manufacturing method therefor

    JP2018012853A

  • Steel plate, plated steel plate, and method for producing the same

    JP6210183B1

  • High-strength steel sheet and method for manufacturing same

    WO2020174805A1